Perlindungan Hak Merek Sebagai Upaya Optimalisasi Pengembangan UMKM Pengrajin Kulit Di Desa Manding Bantul - Wulandari, Cahya; Nihayah, Dyah Maya; Wijayanto, Indung; Rafikawati, Yulia Fajar; Mukhoyyaroh, Vina Durrotul; Rindra, Sarah; Aditya, Agung (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2026)
Manding Village in Bantul Regency is known as a leather craft center with significant creative economic potential. However, most Micro, Small, and Medium Enterprises (UMKM) in the area have limited understanding of trademark protection and registration procedures. This condition weakens product identity and increases the risk of ownership disputes. This community service program aims to improve legal awareness and technical capacity among local entrepreneurs regarding trademark registration as a form of intellectual property rights protection. The methods used were legal education and direct technical assistance with leather craftsmen in Manding. Assistance was provided to two business partners, Crostoso Leather and GUDUKU, covering all registration stages from trademark search, account creation, form completion, to submission via merek.dgip.go.id. The results showed a significant improvement in participants’ understanding and ability to independently register their trademarks. Moreover, legal awareness and motivation to register trademarks increased substantially. This activity contributed to strengthening local product identity and promoting economic independence through intellectual property rights protection.